Analisis Model Prediksi Kebangkrutan Pada Perusahaan Sub Sektor Properti Dan Real Estatee Di Bursa Efek Indonesia Periode 2019 – 2023 - Yunitasari, Nita; Hendriyani, Rina Maria (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the accuracy of the Modified Altman Z-Score, Springate S-Score, and Zmijewski X-Score models in predicting the financial condition of property and real estatee sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. Using a quantitative approach, financial report data from 10 sample companies were analyzed with all three models. The results show that the Modified Altman Z-Score model has an accuracy level of 60%, the Springate S-Score 13%, and the Zmijewski X-Score 60%. The Zmijewski X-Score model proved to be the most suitable in predicting the company's condition for the next two years (2023) compared to other models. The implications of this research highlight the importance of bankruptcy prediction models as an early warning tool for management and investors, and provide recommendations for companies to formulate adaptive strategies in facing potential financial difficulties.